Microplastic interaction with Fe-P coupling pathways induced cadmium immobilization in tropical agricultural soils - Ying Yang; Chaoxian Wei; Pan Pan; Bigui Lin; Zhengfu Yue; Yukun Zou; Beibei Liu (Environmental Pollution, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

Career compromise among nurses in China: A scoping review of current evidence and associated factors - Beibei Liang; Wenwen Liang; Cuixia Lin; Ding Xu (Next Research, 2026)

Stage-dependent roles of Trichoderma longibrachiatum and manganese sulfate in humification and nitrogen conservation during chicken manure composting - Yuchen Yang; Shuzhen Fan; Dan Zhang; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Associations of prenatal exposure to air pollution with fetal growth trajectories phenotype in a cohort study: Implications for child neurodevelopment - Xinmei Chen; Yinting Lin; Yi Lu; Deyi Zhuang; Aifen Zhou; Chenmiao Zhou; Kun Xu; Qinfen Li; Beibei Liu; Wei Xia; Shunqing Xu; Yuanyuan Li; et al. (Journal of Environmental Sciences, 2026)

Superphosphate-driven low-pH regime reduces greenhouse gas emissions during manure composting - Yuchen Yang; Huijie Li; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

Structural characterization and in vivo and in vitro anti-osteoporosis potential of two Psoralea corylifolia L. polysaccharides - Jing Yang; Ziling Tang; Chanjuan Chen; Pei Lin; Ye He; Xinsheng Yao; Beibei Zhang; Zhihong Yao; Zuocheng Qiu; Zifei Qin (Carbohydrate Polymers, 2026)

Artificial Feeds Induce Hepatic Steatosis and Metabolic Reprogramming in Mandarin Fish (Siniperca chuatsi) - Minglin Wu; Yongxu Sun; Yangyang Jiang; Beibei Zhou; Jingwen Hao; Qiang Lin (Fishes, 2026)
Artificial feeds are considered a sustainable alternative to natural live feeds for mandarin fish (Siniperca chuatsi) aquaculture, but their impacts on hepatic metabolism and growth remain unclear. In this study, a total of 800 adult mandarin fish with an initial mean body weight of 152.4 ± 8.7 g were reared for 150 days, and we compared growth performance, liver histology and liver metabolomics of fish fed artificial (AF) or natural live feeds (NF). No significant differences were observed in body length, weight, or condition factor, but the hepatosomatic index (HSI) was significantly higher in the AF group (p

Cephaeline promotes ferroptosis in breast cancer via p53/SLC7A11/GPX4 axis - Xiaohong Li; Jinghan Yu; Beibei Lin; Yudiao Gong (DARU Journal of Pharmaceutical Sciences, 2026)
Background Cephaeline (CPL), a bioactive compound derived from the medicinal plant Ipecacuanha, has demonstrated inhibitory effects on several tumor types. Nevertheless, its role in breast cancer and the underlying molecular mechanisms remain largely unexplored. Objectives This research aimed to investigate the anti-cancer potential of CPL in breast cancer cells. Methods The IC50 of CPL was determined using the CCK-8 assay. Subsequently, the effects of CPL on cell migration and proliferation were assessed through wound healing (scratch) and colony formation assays, respectively. Additionally, MDA and GSH levels were quantified using ELISA, while ROS production was visualized via DHE staining. Intracellular iron content was measured using an iron assay kit. Furthermore, the expression levels of p53, SLC7A11, and GPX4 were evaluated using Western blot. All experiments were performed in triplicate and independently repeated at least three times, and data were analyzed using Student’s t-test or one-way ANOVA, as appropriate. Results CPL significantly inhibited the proliferation and viability of 4T1 and MDA-MB-231 breast cancer cells in a dose-dependent manner, with IC50 values of 38.89 nM and 50.29 nM, respectively, and concomitantly suppressed cell migration and colony formation at higher concentrations. It also increased intracellular MDA and ROS and downregulated GSH, SLC7A11 and GPX4, inducing ferroptosis. siRNA knockdown of p53 attenuated CPL's effects, indicating p53's key role in CPL's anti-cancer activity. Conclusions This study provides evidence that CPL exerts anti-breast cancer effects by promoting ferroptosis through the p53/SLC7A11/GPX4 axis, highlighting its therapeutic potential as a novel agent for cancer treatment.

Genome Analysis and Reproductive Observations Suggest Allotetraploidy and a Potential Reproduction–Metabolism Association in the Endangered Fish Neolissochilus heterostomus - Tiaoyi Xiao; Zhichao Wu; Dongfang Li; Beibei Qin; Shengguo Tang; Chengyi Lin; Kuayun Mao; Jinwu Yin; Zhihu Li; Hongquan Wang; Zhao Lv (Fishes, 2026)
Neolissochilus heterostomus, a cyprinid fish endemic to Yunnan Province, China, is highly valued for both ornamental and edible purposes, yet its wild populations are currently declining and classified as endangered. In this study, we present a chromosome-level genome assembly of N. heterostomus, utilizing the PacBio HiFi and Hi-C strategies. The assembled genome spans 1793.99 Mb and is anchored to 50 chromosomes, comprising a total of 50,203 genes. Genomic features and chromosomal karyotype data recorded in the present study are consistent with an allotetraploid origin for N. heterostomus. Comparative genomics shows that N. heterostomus shares a close phylogenetic relationship with another allotetraploid fish, the common carp Cyprinus carpio. In total, 4687 expanded and 1365 contracted gene families were identified in N. heterostomus. Further enrichment analyses indicated an overrepresentation of metabolism-related pathways among the expanded and positively selected gene families, whereas the contracted gene families were enriched in reproduction- and embryonic development-related pathways. Reproductive observations further indicate that N. heterostomus produces fewer eggs than other cyprinid species characterized by relatively long embryonic development periods (106.1 h; accumulated temperature: 2260.6 °C·h), including common carp, goldfish (Carassius auratus), grass carp (Ctenopharyngodon idella), pond loach (Misgurnus anguillicaudatus), and blunt snout bream (Megalobrama amblycephala). These findings suggest a potential association between metabolism-related genomic features and reproductive traits, although functional validation remains necessary. Overall, this study may offer insights into the polyploidization, metabolic, and reproductive traits of N. heterostomus, thereby providing genomic and biological resources that may support future studies relevant to the conservation and management of this endangered species.

Static magnetic field-assisted impregnation freezing improves crayfish quality: Insights into water mobility and ice crystal morphology - Qiang Li; Yaokun Lu; Jianfeng Lu; Yuan Song; Zhicheng Cai; Beibei Zhou; Lin Lin; Wenhua Miao; Bin Zheng; Changhu Xue (International Journal of Refrigeration, 2026)

Vertical stratification of soil moisture memory and its response to climatic driver factors in inner Mongolia (2001-2024) - Chaofan Zhou; Huili Gong; Beibei Chen; Xiaojuan Li; Lin Zhu; Mengxuan Bao; Jiajun Zhu (Journal of Arid Environments, 2026)

Advancements and future perspectives in blueberry processing technology - Jianjun Guo; Xihong Li; Lijun Lin; Beibei Zhang; Yudian Xu; Piao Zhou; Xin Xu (Food and Humanity, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Environmental risks and upcycling potential in ternary geopolymer development for oily sludge pyrolysis byproducts - Chenxu Zhong; Chujun Luan; Xuan Guo; Fawei Lin; Jingwei Li; Beibei Yan; Zhanjun Cheng; Eminov Ashraf Mamurovich; Bigaliev Aitkhazha Bigalievich; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Manure-driven antibiotic resistance in agroecosystems: Decadal evidence of accumulation dynamics and food chain transmission - Shuang Peng; Shaoying Xu; Beibei Zhou; Qingqing Hua; Pan Wu; Xiangui Lin; Yiming Wang (Journal of Hazardous Materials, 2026)

How Kuroshio current, Tsushima warm current, and Yellow Sea warm current co-evolved since the middle Holocene - Xiaochuan Ma; Lingjing Xu; Dezhou Yang; Beibei Mi; Lin Jia; Fengming Chang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Comparative study by microwave, fixed-bed and rotary kiln pyrolysis of oily sludge: Petroleum hydrocarbons, N-/S-/Cl-containing pollutants and heavy metals - Jiantao Li; Hongdi Yu; Fawei Lin; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Guijian Liu; Xiaojiang Shen; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

Photochemistry of acetylacetone: Droplets-mediated H2O2 generation and SO2 oxidation - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Enhancing ship energy efficiency through just-in-time arrival: A comprehensive review - Songyin Yan; Wuliu Tian; Bowen Lin; Beibei Meng; Simon Larsson; Jingxuan Tian (Ocean Engineering, 2025)

Radical reaction-wastewater fuel cell with Fe-modified graphene hydrogel particle electrodes - Tingsheng Zhou; Panyu Jiang; Jinhua Li; Yan Zhang; Lei Li; Beibei Li; Chaoyue Xie; Jia Lin; Jing Bai; Mingce Long; Baoxue Zhou (Journal of Hazardous Materials, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

The effect of photosensitization reaction of imidazole-2-carbaldehyde on the heterogeneous uptake of sulfur dioxide on hematite - Yixuan An; Lingdong Kong; Beibei Liu; Jiandong Shen; Yu Lu; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Environment, 2025)

Characteristics and influencing factors of ambient ozone pollution in Hangzhou in the relative humidity range with high ozone levels - Yu Lu; Lingdong Kong; Jiandong Shen; Beibei Liu; Yixuan An; Yuwen Wang; Jie Tan; Lin Wang (Atmospheric Pollution Research, 2025)

CuO/M(OH)₂ (M = Mg, Ca) heterostructures with in-situ oxygen vacancies enable room-temperature ultrahigh triethylamine sensing - Ruixiang Li; Shu Chen; Beibei Wang; Xiaodan Wang; Xinyu Hu; Sonia Estrade Albiol; Cristian Fabrega Gallego; Hao Shen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Aqueous photochemistry of brown carbon: H2O2 formation, enhanced SO2 oxidation, and the real role of excited triplets - Beibei Liu; Lingdong Kong; Yixuan An; Yu Lu; Yuwen Wang; Jie Tan; Xingfu Tang; Lin Wang (Atmospheric Environment, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

From biodegradation to biohazard: Polylactic acid microplastics induced rice growth inhibition in agroecosystems - Bigui Lin; Qingfang Fan; Fang Liu; Luya Wang; Chaoxian Wei; Beibei Liu; Juan Zhao; Linzi Zuo; Yi Xie (Journal of Hazardous Materials, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Maize biomass estimation by integrating spectral, structural, and textural features from unmanned aerial vehicle data - Lin Meng; Bo Ming; Yuan Liu; Chenwei Nie; Liang Fang; Lili Zhou; Jiangfeng Xin; Beibei Xue; Zhongyu Liang; Huirong Guo; Dameng Yin; Xiuliang Jin (European Journal of Agronomy, 2025)

Ignition, combustion and pollutant emissions characteristics of excavated waste in low oxygen concentration and O2/CO2 atmosphere - Jingwen Lv; Beibei Yan; Shengquan Zhou; Zhaoting Wu; Xiaoyun Liu; Sensen Lu; Xiaochao Zhu; Yunan Sun; Jian Li; Fawei Lin; Guanyi Chen (Waste Management, 2025)

Effects of soil moisture fluctuation and microplastics types on soil organic matter decomposition and carbon dynamics - Junjie Lin; Beibei Chen; Hongxin Dong; Wenling Zhang; Amit Kumar; Dafeng Hui; Changai Zhang; Shengdao Shan; Biao Zhu (Soil Biology and Biochemistry, 2025)

Effective feature matching of high-resolution planetary orbiter images based on optimized image partitioning and rapid local correspondence - Lin Xue; Zhen Ye; Dayong Liu; Shijie Liu; Rong Huang; Huan Xie; Yongjiu Feng; Beibei Guo; Yusheng Xu; Xiaohua Tong (Planetary and Space Science, 2025)

Life cycle assessment of anaerobic digestion coupled co-pyrolysis for treatment of food waste - Juan Zhao; Jingxin Zhao; Zhi Wang; Siyu Lin; Beibei Yan; Guanyi Chen; Wenhe Zhou (Bioresource Technology, 2025)

Multi-model fusion method for predicting CO2 concentration in greenhouse tomatoes - Jianjun Guo; Beibei Zhang; Lijun Lin; Yudian Xu; Piao Zhou; Shangwen Luo; Yuhan Zhuo; Jingyu Ji; Zhijie Luo; Shahbaz Gul Hassan (Computers and Electronics in Agriculture, 2024)

Western diet induces GSDME-mediated epithelial pyroptosis through the DCA-S1PR2 pathway to disrupt the intestinal epithelial barrier - Ke Liu; Mengyao Song; Xueqin Huang; Yanqiang Shi; Sheng Li; Fangqing Zhu; Teng Ben; Xinlong Lin; Bingxia Chen; Beibei Xu; Sicong Ma; Binhai Shen; et al. (Science Bulletin, 2024)

Transcriptome analysis of hepatopancreas revealed the role of autophagy under nitrite stress in Pacific white shrimp (Penaeus vannamei) - Xinghao Lin; Zhengxinyu Liu; Jiaqian Chen; Xiaotong Huang; Wanghao Du; Yu Zhang; Beibei Dong; Qingjian Liang (Aquaculture International, 2024)

Microbial groups containing alkaline phosphatase accelerate soil phosphate mineralization in two soil patterns with contrasting pH levels - Hui Li; Jitong Lin; Qi Shao; Beibei Zhang; Yunting Wang; Linke Wang; Haojie Feng; Yanhong Lou; Hui Wang; Quangang Yang; Zhongchen Yang; Hongjie Di; et al. (Journal of Soils and Sediments, 2024)

Differences in the uptake and translocation of differentially charged microplastics by the taproot and lateral root of mangroves - Yichun Lin; Luya Wang; Bigui Lin; Beibei Liu; Tingting Guan; Shuai Guo; Qinfen Li; Chaoxian Wei (Science of The Total Environment, 2024)

Green transformation of oily sludge through geopolymer: Material properties and hydration mechanisms - Xuan Guo; Hongdi Yu; Hongyun Yao; Fawei Lin; Eslam Salama; Mona Ossman; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Intelligent technologies powering clean incineration of municipal solid waste: A system review - Junyu Tao; Zaixin Li; Chao Chen; Rui Liang; Shuang Wu; Fawei Lin; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2024)

Priming effects of surface soil organic carbon decreased with warming: a global meta-analysis - Hongxin Dong; Junjie Lin; Jiayu Lu; Lujun Li; Zhiguo Yu; Amit Kumar; Qin Zhang; Dan Liu; Beibei Chen (Plant and Soil, 2024)

Direct aqueous photochemistry of methylglyoxal and its effect on sulfate formation - Jie Tan; Lingdong Kong; Yuwen Wang; Beibei Liu; Yixuan An; Lianghai Xia; Yu Lu; Qing Li; Lin Wang (Science of The Total Environment, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Assembly mechanisms and driving factors of aerobic denitrifying bacteria community with different seasons and rarity in the sediments of Baiyangdian Lake - Zhaoying Chen; Tinana Zhang; Ziwei Zhang; Lin Yue; Jiansheng Cui; Jiafeng Zhang; Shilei Zhou; Beibei Chai (Journal of Soils and Sediments, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Health assessment based on exposure to microplastics in tropical agricultural soil - Bigui Lin; Luya Wang; Qiyu Chen; Zhilei Liu; Beibei Liu; Shaobai Wen; Fang Liu; Xichao Chen; Zongyao Zhang; Lin Wu; Chaoxian Wei (Journal of Hazardous Materials, 2024)

Sustainable supply chain planning with the flexible provisions of inter-period emission credits borrowing and banking under a multi-period carbon trading scheme - Minke Wang; Beibei Ye; Shuang Lin; Chaofeng Wang; Peiwen Zhang (Journal of Cleaner Production, 2024)

Benzoquinone and furopyridinone derivatives from the marine-derived fungus Talaromyces sp. MCCC 3A01752 - Xuan Hong; Lingzhi Tang; Zhongwei Chen; Qiliang Lai; Beibei Zhang; Youwei Jiang; Xunjie Wang; Ruonan He; Jianhui Lin; Zongze Shao; Shan Lin; Weiyi Wang (Natural Product Research, 2024)

BDE-47 induces metabolic dysfunction-associated steatotic liver disease (MASLD) through CD36-mediated increased fatty acid uptake and PPARα-induced abnormal fatty acid oxidation in BALB/c mice - Beibei Xia; Rongfei Yu; Junxiong Liu; Dongmeng Liu; Shasha Li; Liu Yang; Nan Liu; Bosen Liang; Jiajing Zeng; Jinhua Wei; Guimiao Lin (Toxicology Letters, 2024)

Fe(Ⅲ) concentrations controlled highly soluble carboxylated inulin–Fe toward efficient supplement of iron - Yuhuan Zhang; Beibei Wang; Chunmeng He; Lin Shi; Jianke Li (Food Hydrocolloids, 2023)

Endophyte inoculation enhanced microbial metabolic function in the rhizosphere benefiting cadmium phytoremediation by Phytolacca acinosa - Bing Li; Beibei Wu; Yingbo Dong; Hai Lin; Chenjing Liu (Chemosphere, 2023)

Downregulation of XBP1s aggravates lipopolysaccharide-induced inflammation by promoting NF-κB and NLRP3 pathways’ activation in goat endometrial epithelial cells - Kangkang Gao; Yanyan Yi; Zhongqiang Xue; Zongjie Wang; Shan Huang; Beibei Zhang; Pengfei Lin; Aihua Wang; Huatao Chen; Yaping Jin (Theriogenology, 2023)

Excessive dietary soluble arabinoxylan impairs the intestinal physical and immunological barriers via activating MAPK/NF-κB signaling pathway in rainbow trout (Oncorhynchus mykiss) - Junming Deng; Xindang Zhang; Beibei Lin; Haifeng Mi; Lu Zhang (Fish & Shellfish Immunology, 2023)

The role of pores in micro-zone distribution of Cd in a tropical paddy soil: Results from X-ray computed tomography combined energy dispersive spectroscopy analysis - Chaoxian Wei; Bigui Lin; Beibei Liu; Zhenli He; Qinfen Li (Journal of Hazardous Materials, 2023)

An unrecognized entry pathway of submicrometre plastics into crop root: The split of hole in protective layer - Luya Wang; Beibei Liu; Wen Zhang; Qinfen Li; Bigui Lin; Chaoxian Wei (Journal of Hazardous Materials, 2023)

La0.7(Ca, Sr)0.3Ni0.6Mn0.5O3 perovskites for photothermal catalytic reforming of toluene: The role of oxygen species in the photothermal synergistic effect - Xiaoshan Dong; Jian Wang; Fawei Lin; Jian Li; Tianxiao Yu; Beibei Yan; Guanyi Chen (Fuel, 2023)

Land subsidence simulation based on Extremely Randomized Trees combined with Monte Carlo algorithm - Zijian Wang; Lin Guo; Huili Gong; Xiaojuan Li; Lin Zhu; Ying Sun; Beibei Chen; Xueqi Zhu (Computers & Geosciences, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Pyrolysis/combustion potential and heavy metal risk of oily sludge and derived products in industrial scale - Hongdi Yu; Jiantao Li; Fawei Lin; Menglan Zeng; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2023)

Polystyrene microplastics enhance the microcystin-LR-induced gonadal damage and reproductive endocrine disruption in zebrafish - Wang Lin; Huimin Luo; Jingyi Wu; Xiangli Liu; Beibei Cao; Yuqing Liu; Pinhong Yang; Jifeng Yang (Science of The Total Environment, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

Necessity of introducing particle size distribution of hand-adhered soil on the estimation of oral exposure to metals in soil: Comparison with the traditional method - Beibei Wang; Fei Gao; Yujie Li; Chunye Lin; Hongguang Cheng; Xiaoli Duan (Journal of Hazardous Materials, 2023)

Embedding Co in perovskite MoO3 for superior catalytic oxidation of refractory organic pollutants with peroxymonosulfate - Qingyi Zeng; Jing Tan; Beibei Gao; Tao Cai; Qingyan Zhang; Yi-Lin Liu; Sheng Chang; Shuaifei Zhao; Suqing Wu (Chemosphere, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

A highly-sensitive sensor based on carbon nanohorns@reduced graphene oxide coated by gold platinum core–shell nanoparticles for electrochemical detection of carbendazim in fruit and vegetable juice - Wenzhe Li; Peixuan Wang; Beibei Chu; Xingguang Chen; Zhengcong Peng; Jiyang Chu; Rui Lin; Qianhui Gu; Jian Lu; Dianhui Wu (Food Chemistry, 2023)

UV–vis-enhanced photothermal catalytic reforming of biomass model tar via LaMnxNi1-xO3 perovskite catalyst - Xiaoshan Dong; Xiaochao Zhu; Fawei Lin; Beibei Yan; Jian Li; Guanyi Chen (Chemical Engineering Journal, 2023)

Response of cadmium adsorption to three-year different agronomic managements in tropical soil: The role of P fractions and Fe oxides - Beibei Liu; Chaoxian Wei; Dengxiu Wei; Miao Chen; Wei Li; Pan Pan; Bigui Lin; Lin Wu; Qinfen Li; Zhenli He (Agriculture, Ecosystems & Environment, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Phosphorus fractions and iron oxides responsible for the variations in the Cd retention capacity in tropical soil aggregates under different cropping patterns - Dengxiu Wei; Chaoxian Wei; Pan Pan; Bigui Lin; Lin Wu; Beibei Liu; Zhenli He (Journal of Hazardous Materials, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Structure elucidation of a novel cyclic tripeptide from the marine-derived fungus Aspergillus ochraceopetaliformis DSW-2 - Yanyan Liao; Xuan Hong; Jing Yang; Jiang-Jiang Qin; Beibei Zhang; Jianhui Lin; Zongze Shao; Weiyi Wang (Natural Product Research, 2022)

Is hand-to-mouth contact the main pathway of children’s soil and dust intake? - Yiwei Gong; Yihang Wu; Chunye Lin; Dongqun Xu; Xiaoli Duan; Beibei Wang; Xitao Liu; Hongguang Cheng; Qin Wang; Jin Ma (Environmental Geochemistry and Health, 2022)

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Hydrogen alleviates cell damage and acute lung injury in sepsis via PINK1/Parkin-mediated mitophagy - Hongguang Chen; Huaying Lin; Beibei Dong; Yaoqi Wang; Yonghao Yu; Keliang Xie (Inflammation Research, 2021)

The metabolic changes in the hippocampus of an atherosclerotic rat model and the regulation of aerobic training - Beibei Liu; Jingjing Li; Xiaojing Lin; Jingyun Hu; Shujie Lou (Metabolic Brain Disease, 2020)

Protective Effects of Salidroside on Lead Acetate-induced Oxidative Stress and Hepatotoxicity in Sprague-Dawley Rats - Chen Chen; Beibei Lin; Shanshan Qi; Jia He; Hongxing Zheng (Biological Trace Element Research, 2019)

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

Total arsenic concentrations in Chinese children’s urine by different geographic locations, ages, and genders - Xuan Zhang; Beibei Wang; Xiaoyong Cui; Chunye Lin; Xitao Liu; Jin Ma (Environmental Geochemistry and Health, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Characterization and causes of land subsidence in Beijing, China - Beibei Chen; Huili Gong; Xiaojuan Li; Kunchao Lei; Lin Zhu; Mingliang Gao; Chaofan Zhou (International Journal of Remote Sensing, 2017)

Properties of root exudates and rhizosphere sediment of Bruguiera gymnorrhiza (L.) - Beibei Liu; Xinyu Liu; Shanshan Huo; Xin Chen; Lin Wu; Miao Chen; Kaibo Zhou; Qinfen Li; Lixu Peng (Journal of Soils and Sediments, 2017)

The application of rapidly composted manure decreases paddy CH4 emission by adversely influencing methanogenic archaeal community: a greenhouse study - Beibei Zhou; Yiming Wang; Youzhi Feng; Xiangui Lin (Journal of Soils and Sediments, 2016)

Bacteria play a more important role than nutrients in the accumulation of tetracycline resistance in manure-treated soil - Shuang Peng; Beibei Zhou; Yiming Wang; Xiangui Lin; Hongmei Wang; Cunpu Qiu (Biology and Fertility of Soils, 2016)

Three isoforms of the Atg16L1 protein contribute different autophagic properties - Tao Jiang; Beibei Qin; Jianqin He; Shuangyan Lin; Shiping Ding (Molecular and Cellular Biochemistry, 2013)

Acoustically evoked short latency negative responses in hearing loss patients with enlarged vestibular aqueduct - Lin Liu; Beibei Yang (Acta Neurologica Belgica, 2013)